2007
DOI: 10.1063/1.2800316
|View full text |Cite
|
Sign up to set email alerts
|

Product branching between reactive and nonreactive pathways in the collisional quenching of OH AΣ+2 radicals by H2

Abstract: The collisional quenching of OH radicals in their excited A 2Sigma+ electronic state by molecular hydrogen is examined to determine the partitioning between reactive and nonreactive pathways. This is achieved using a pump-probe laser technique to compare the population prepared in the excited OH A 2Sigma+ state with that produced in the OH X 2Pi ground state from nonreactive quenching. Only a small fraction of the products, less than 15%, arise from nonreactive quenching; reactive quenching is the dominant pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
63
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(77 citation statements)
references
References 17 publications
11
63
1
2
Order By: Relevance
“…The nonreactive quenching channel has also been investigated recently in Lester's experiments, utilizing a pump-probe approach in the collisional region of a supersonic free-jet expansion. [11][12][13][14] The OH products were generated with significant rotational excitation, but small degree of vibrational excitation, and the preference for reactive quenching over nonreactive quenching by roughly 7 to 1 was also discovered by the Lester group. 13 Theoretically, Yarkony and co-workers performed stateaveraged multiconfigurational self-consistent field/ configuration interaction calculations to determine the conical intersections ͑CoIs͒ of the potential energy surfaces ͑PESs͒ relevant to this quenching.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…The nonreactive quenching channel has also been investigated recently in Lester's experiments, utilizing a pump-probe approach in the collisional region of a supersonic free-jet expansion. [11][12][13][14] The OH products were generated with significant rotational excitation, but small degree of vibrational excitation, and the preference for reactive quenching over nonreactive quenching by roughly 7 to 1 was also discovered by the Lester group. 13 Theoretically, Yarkony and co-workers performed stateaveraged multiconfigurational self-consistent field/ configuration interaction calculations to determine the conical intersections ͑CoIs͒ of the potential energy surfaces ͑PESs͒ relevant to this quenching.…”
Section: Introductionmentioning
confidence: 93%
“…[11][12][13][14] The OH products were generated with significant rotational excitation, but small degree of vibrational excitation, and the preference for reactive quenching over nonreactive quenching by roughly 7 to 1 was also discovered by the Lester group. 13 Theoretically, Yarkony and co-workers performed stateaveraged multiconfigurational self-consistent field/ configuration interaction calculations to determine the conical intersections ͑CoIs͒ of the potential energy surfaces ͑PESs͒ relevant to this quenching. [17][18][19] Further theoretical work by Hoffman and Yarkony has located 13 conical intersections between the AЈ surfaces involved in the quenching dynamics.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…There has been extensive experimental and theoretical interest in this system: experiments based on two-photon laser-induced fluorescence and crossed molecular beam scattering have demonstrated that a large part of the electronic energy is partitioned into excitations of the internal vibrational modes of the water products. [35][36][37][38] However, final state distributions were not determined. Theoretically, relevant work on this quenching has been done by Yarkony and co-workers, using multiconfigurational SCF and CI calculations to determine the conical intersections.…”
Section: Final State Distributionsmentioning
confidence: 99%
“…These reactions (and isotopic analogues) have generated substantial experimental interest in recent years. [8][9][10][11][12][13][14][15][16][17] Moreover, there has been significant theoretical interest in the electronic structure and conical intersections of this system, 10,18,19 and in the general question of adiabatic to diabatic transformations (ADTs) in molecules with conical intersections. [20][21][22][23][24] As a consequence, this system represents a benchmark test case for the development of theoretical reaction dynamics for polyatomic molecules in multiple electronic states.…”
Section: Introductionmentioning
confidence: 99%